ANALISA PERILAKU KONSUMSI AIR MINUM DAN KEPEDULIAN TERHADAP KEBERLANJUTAN PADA MAHASISWA UNIVERSITAS SWASTA STRATA 1 DI KABUPATEN TANGERANG - Andrian, Andrian; Bawono, Gasza Ariatedya; Mujaddid, Nugraha Labib; Rafsanjhani, Muhammad Akbar; Simatupang, Parhimpunan (JURNAL LENTERA BISNIS, 2026)
Single-use bottled water consumption remains high among students despite health risks. This  study  aims  to  analyze  the  determinants  of  drinking  water  consumption behaviour among private university students in South Tangerang, focusing on knowledge, convenience, risk perception, social norms, and behavioral control. Employing a quantitative explanatory approach, data were collected from 183 students via online questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) using SmartPLS software. The results indicate that Environmental Knowledge has a significant negative effect, while Convenience has a significant positive effect and serves as the dominant factor. Risk Perception regarding alternative water sources also contributes to high bottled water consumption. However, Social Norms did not show a significant effect, whereas   Infrastructure   demonstrated   a   significant   negative   effect   on   consumption behaviour. It is concluded that high plastic consumption is driven by low-risk literacy and a high demand for practicality. Campus interventions must focus on massive health education and providing Water Refill Stations that compete with the convenience of bottled water.